Local scour around submarine pipelines under wave conditions - Cevik, EO; Yuksel, Y (INTERNATIONAL SOCIETY OFFSHORE& POLAR ENGINEERS, 1997)
Experiments have been carried out to determine the scout depth below submarine pipelines that are placed rigid position on bed under only wave conditions. The relative scout depth depends on Keulegan-Carpenter number (KC) Pad frequency parameter (beta) and their ranges are 1.31 and 35, 3.5x10(2) and 1.3x10(4) respectively. Experimental results agree with the precious works with variation KC number of the relative scout depth. It was found that the relative scout depth is also proportional to the frequency parameter and the grain size gradation doesn't affect the scour depth below the submarine pipelines.
Keywords: local scour; submarine pipelines; seabed interaction; Engineering